Activation of TGF-β signaling induces cell death via the unfolded protein response in Fuchs endothelial corneal dystrophy - Okumura, Naoki; Hashimoto, Keisuke; Kitahara, Miu; Okuda, Hirokazu; Ueda, Emi; Watanabe, Kyoko; Nakahara, Makiko; Sato, Takahiko; Kinoshita, Shigeru; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; et al. (Scientific Reports, 2017)
Fuchs endothelial corneal dystrophy (FECD) is a slowly progressive bilateral disease of corneal endothelium in which accumulation of extracellular matrix (ECM) and loss of corneal endothelial cells (CECs) are phenotypic features. The corneal endothelium maintains corneal transparency by regulating water hydration; consequently, corneal endothelial dysfunction causes serious vision loss. The only therapy for corneal haziness due to corneal endothelial diseases, including FECD, is corneal transplantation using donor corneas, and no pharmaceutical treatment is available. We provide evidence that the expression levels of transforming growth factor-? (TGF-?) isoforms and TGF-? receptors are high in the corneal endothelium of patients with FECD. A cell model based on patients with FECD shows that TGF-? signaling induced a chronic overload of ECM proteins to the endoplasmic reticulum (ER), thereby enhancing the formation of unfolded protein and triggering the intrinsic apoptotic pathway through the unfolded protein response (UPR). We propose that inhibition of TGF-? signaling may represent a novel therapeutic target that suppresses cell loss as well as the accumulation of ECM in FECD.
EVALuna2:21350